Dogs don't tell jokes - Sachar, Louis, 1954- (New York : Yearling, 2004)
Twelve-year-old Gary, known as Goon because of his constant clowning and joke-telling, tries to change his image and make new friends at school.
3.8
3-6
3-6
Wilson's Junior High School
Elem. School Library Collection
School Library Journal
Keywords: Schools -- Juvenile fiction; Self-perception -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Fiction; Self-perception -- Fiction; Friendship -- Fiction; School stories; Self-perception -- Fiction; Friendship -- Fiction